Respostas

A melhor resposta!
2014-05-01T20:40:44-03:00


x²- 4x + 3< 0
Δ=b²-4ac
Δ=(-4)²-4(1)(3)
Δ=16-12
Δ=4 >0
      
x1=
 -b-√Δ       -(-4) - √4           4 - 2            2                              1     3
      ---------- =  --------------- = ---------------- = --------- =  1                    |      |
         2a              2(1)              2               2                         +    |      |    +
                                                                                       -------•\/\/\/•-------
x2 = 
-b+√Δ       -(-4) + √4          4+2            6                             \   -  /
      ------------- = ----------------- =  ---------- =  ---------- = 3                     
            2a             2(1)               2              2   

V={x∈R| 1 ≤ x ≤ 3} = [1;3]




x² - 7x +10 > 0
Δ=b²-4ac
Δ=(-7)²-.4(1)(10)
Δ=49 - 40
Δ=9 > 0

x1= -b-√Δ       -(-7) -√9        7 - 3       4                                    2        5
      ---------- = --------------- = ---------- = ------ = 2                            |         |
         2a              2(1)            2         2                                  + |        |   +
                                                                                     /\/\/\/\•-------•/\/\/\/\/\/\
x2= -b+√Δ       -(-7) +√9         7+3           10                              \   -   /
      ----------- = ---------------- = ------------ = ----------- = 5
          2a             2(1)               2             2

V={x∈R|x≤2 ou x≥5} = ]-∞;2] U [5;+∞[
1 5 1